Voices of migrants : rural-urban migration in Costa Rica - Kutsche, Paul, 1927- (University Press of Florida, 1994)
"Verbatim or near-verbatim 1981-84 interviews with 14 Costa Ricans (ten men, four women) provide information about life histories of migrants to San José. Strong opening chapters provide the context for migration and the interview-years. Conclusion relates their narratives to Costa Rican 'exceptionalism' and other value-patterns"--Handbook of Latin American Studies, v. 57.